P14. Local diagnostic reference levels for barium enemas, swallows and meals. (September 2016) - Behardien-Peters, N.; Davidson, F.; Kotze, T.; Trauernicht, C.
Abstract : Introduction: Diagnostic reference levels (DRLs) are dose levels for typical examinations of groups of standard-sized patients. Patient doses can only be managed if the magnitude and range of doses encountered for a study are known. DRLs can then be set using this data and local practice can be improved by comparing the institution's data with appropriate DRLs. The DRL is usually set at the 75th percentile of the distribution of doses for a particular examination. This study looks at the doses patients received for barium enemas, swallows and meals at Groote Schuur Hospital. Method and materials: DAP readings were recorded for the three procedures from March 2012 to July 2015. Patients weighing between 50 and 90 kg were included in this study. This resulted in 34 barium swallows, 35 barium meals and 41 barium enemas. DAP readings were sorted from smallest to largest and the diagnostic reference level for each procedure was set at the third quartile of the distribution. Results: The DRLs obtained in this study are: barium enema – 16.0 Gy·cm 2, barium swallow – 12.8 Gy·cm 2 and barium meal – 17.4 Gy·cm 2 . Conclusion: Based on previously published data there was a significant improvement of the DRL for the barium enema (previously published local DRL of 36.5 Gy·cm 2 ), with some reduction in the DRL for the barium meal studies (down from 20.1 Gy·cm 2 ). A first local DRL for the barium swallow was established.